2007
DOI: 10.1017/s0265021506002018
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine 0.75% vs. lidocaine 4% for topical anaesthesia

Abstract: Topical levobupivacaine 0.75% shows the same efficacy and safety as lidocaine 4% in cataract surgery by phacoemulsification. There was an adequate block with a good level of satisfaction of surgeon and patients. Levobupivacaine 0.75% offers a new and acceptable choice for topical anaesthesia in cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Di Donato et al 22 in their recent study of 203 patients undergoing phacoemulsification surgery, clinically compared the efficiency of levobupivacaine 0.75% and lidocaine 4% as topical anaesthetic, and found that topical levobupivacaine 0.75% had the same efficacy and safety as lidocaine 4% in cataract surgery by phacoemulsification. There was an adequate block with a good level of satisfaction of surgeon and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Donato et al 22 in their recent study of 203 patients undergoing phacoemulsification surgery, clinically compared the efficiency of levobupivacaine 0.75% and lidocaine 4% as topical anaesthetic, and found that topical levobupivacaine 0.75% had the same efficacy and safety as lidocaine 4% in cataract surgery by phacoemulsification. There was an adequate block with a good level of satisfaction of surgeon and patients.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Although levobupivacaine is routinely used to provide regional anaesthesia, the results of clinical studies on its topical administration for ophthalmic surgery appears in only one study. 22 In this study, we evaluated and compared the efficacy of topical application of lidocaine 2%, levobupivacaine 0.75%, and ropivacaine 1% in patients undergoing cataract surgery with phacoemulsification. The present study is the first report of a comparison of the effects of these three topical anaesthetic agents in cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Lidocaine, ropivacaine, and levobupivacaine are 3 commonly used topical anesthetic agents in modern cataract surgery. [7][8][9] Topical anesthesia does not provide adequate motor and sensory anesthesia and may be associated with increased intraoperative pain and complications. 4 Therefore, intracameral injection of unpreserved lidocaine 1% has become a commonly used adjunctive anesthetic agent during cataract surgery.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27] There is only a single report in the literature that presents the effects of intracameral ropivacaine in rabbit eyes. 28 Although there has been ongoing research on the use of levobupivacaine for topical anesthesia, 7,8 intracameral application of this agent has not been studied. Therefore, the purpose of this study was to quantify and compare the effects of intracameral injection of 3 anesthetic agentsdpreservativefree lidocaine hydrochloride 2%, ropivacaine 1%, and levobupivacaine 0.75%don the rabbit corneal endothelium.…”
mentioning
confidence: 99%
“…12 Pa ti ent sa tis fac ti on was re ported as 83% in li do ca i ne-bu pi va ca i ne tre a ted gro up and 97% in ro pi va ca i ne tre a ted gro up in a study which com pa red pe ri bul bar anest he si a with eit her 0.75% ro pi va ca i ne or 2% li do ca i ne-0.5% bu pi va cai ne mix tu re for vit re o re ti nal sur gery. 13 In anot her study, re se arc hers re por ted a trend to wards bet ter sa tis fac ti on in pa ti ents ad mi nis te red le vo bu pi va cai ne com pa red to ro pi va ca i ne at 24 ho urs fol lo wing ope ra ti on.…”
Section: Discussionunclassified